Quantifying treatment response to a macrophage-targeted therapy in combination with immune checkpoint inhibitors after exposure to conventional chemotherapy - Bess, Shelby N.; Smart, Gaven K.; Muldoon, Timothy J. (Frontiers in Immunology, 2025)
BackgroundConventional chemotherapeutic agents, such as 5-fluorouracil (5-FU), can exert anti-tumor effects through immunogenic cell death (ICD) induction. Researchers have found hallmarks that quantify ICD (such as the translocation of HMGB1 and calreticulin). Although chemotherapeutic agents can induce ICD, they increase the expression of immune checkpoints, limiting their effectiveness. Studies have emphasized the importance of investigating the heterogeneous responses of cells co-localized in a solid tumor (macrophages, tumor cells, etc.) to ICD induction. However, these studies were performed in vivo, which limits the collection of information on cell-cell interactions due to model complexity.MethodsIn this study, we used a multicellular spheroid model in conjunction with single spheroid imaging to understand the structural and metabolic changes of a simulated solid tumor model. In addition to using the spheroid model, conventional 2D co-culture monolayers were used to quantify ICD hallmarks and changes in macrophage functional behavior while correlating immune responses after exposure to the combinatory regimen of immune checkpoint inhibitors and an ICD inducer.ResultsResults indicate that the combination of two immune checkpoint inhibitors in addition to a chemotherapy agent reduced spheroid growth (~46%) and reduced M2 macrophage expression and cellular proliferation while modulating cellular metabolism, ICD hallmarks, and phagocytic function.ConclusionsOverall, this study not only quantified microregional metabolic and structural changes in a simulated spheroid model but also quantified changes in ICD hallmarks and macrophage functional behavior. It was also found that correlations between spheroid structure and ICD hallmarks through immunofluorescence markers could exist after exposure to the combinatory regimen of immune checkpoint inhibitors and an ICD inducer.